(untitled) (Bangladesh Critical Care Journal, 2021)
Lithium Carbonate is the first line treatment for bipolar depressive disorder. It also has beneficial effects on prophylactic use in Acute manic episodes to prevent recurrence and reduces rate of suicide associated with affective disorder. Low therapeutic index of Lithium (0.8-1.2meq/l) mandates regular and frequent measurement of Serum lithium level in patients taking this drug. Here we present a 59 years Indian male who is a known diabetic, chronic alcoholic and a case of bipolar disorder. He was on Lithium tablet off and on for last 4 years and was also on oral antidiabetic agent. He was admitted in ICU through emergency with complaints of altered level of consciousness for 2 days with H/O recurrent hypoglycemia associated with nausea, reduced food intake, vertigo, tremor of all four limbs with weakness of both lower limbs for approximately last 2 months. Admission serum lithium level was 2.24meq/l. Hemodialysis was started. Neurological symptoms improved and serum Lithium level returned to normal (0.79meq/l) after 2 session of hemodialysis. Bangladesh Crit Care J March 2021; 9(1): 46-48